The Evaluation of The Character Education Program in Muhammadiyah Elementary Schools - Sholawati Sholawati; Akif Khilmiyah (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Character education is the core of the implementation of education in general. The school's character education was planned and well carried out, but the evaluation was not maximum. Thus, the study was to evaluate the character education programs at schools, especially the Islam-based elementary school - the Muhammadiyah elementary school in the Kalasan district. This research is evaluation research that uses a mixed method (Qualitative and Quantitative) approach. The study was conducted at 4 Muhammadiyah elementary schools in the Kalasan district. Assessments of context, input, process, and product character education programs. Data collection involves interviews, observations, documentation, and attitude assessments using elementary school emotional and social intelligence (Penilaian Kecerdasan Emosional dan Sosial-PKesSD) applications. Studies show that the program input is excellent. Whereas the character education program's context, process, and product fall into good categories. The result of the average spiritual and social attitude assessment of the student scores above 3 which means good. The evaluation of emotional and social intelligence suggests that in both affective and psychomotor aspects, students have high levels of intelligence and moderate cognitive. This means that students have been very good at feeling and acting out the character values they have been taught, but students have not yet understood fully why they do such a thing.